2012
DOI: 10.1159/000338440
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Xylitol on Blood Glucose, Glucose Tolerance, Serum Insulin and Lipid Profile in a Type 2 Diabetes Model of Rats

Abstract: Background/Aims: The present study was conducted to examine the antidiabetic effects of xylitol in a type 2 diabetes rat model. Methods: Six-week-old male Sprague-Dawley rats were randomly divided into 3 groups: normal control (NC), diabetic control (DBC) and xylitol (XYL). Diabetes was induced only in the DBC and XYL animal groups by feeding them a 10% fructose solution for 2 weeks followed by an injection (i.p.) of streptozotocin (40 mg/kg body weight). One week after the streptozotocin injection, the animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 66 publications
6
32
0
5
Order By: Relevance
“…9 The present study was conducted to investigate possible mechanisms behind the anti-diabetic effects of xylitol using several in vitro, ex vivo and in vivo models. The lower caloric value (2.4 kcal vs. 4.0 kcal g −1 ), insulinemic response, and glycemic index (13 vs. 65) but similar sweetness compared to sucrose has made it more popular to people, especially diabetics.…”
Section: Food and Function Papermentioning
confidence: 99%
See 2 more Smart Citations
“…9 The present study was conducted to investigate possible mechanisms behind the anti-diabetic effects of xylitol using several in vitro, ex vivo and in vivo models. The lower caloric value (2.4 kcal vs. 4.0 kcal g −1 ), insulinemic response, and glycemic index (13 vs. 65) but similar sweetness compared to sucrose has made it more popular to people, especially diabetics.…”
Section: Food and Function Papermentioning
confidence: 99%
“…9 It has also been reported that faster intestinal transit and delayed gastric emptying might be the cause of the slower intestinal nutrient absorption and the reduced food intake. 9 It has also been reported that faster intestinal transit and delayed gastric emptying might be the cause of the slower intestinal nutrient absorption and the reduced food intake.…”
Section: Food and Function Papermentioning
confidence: 99%
See 1 more Smart Citation
“…[19] This effect is due to the insulin-independent metabolism of xylitol that can be used to replace sugar on weight/weight basis. [22] This further shows that xylitol does, in fact, can be used as a supplement both in preventing unwanted effects in normal as well as diabetic populations.…”
Section: Discussionmentioning
confidence: 99%
“…[18] A study on Sprague-Dawley rats were done to determine the effects of xylitol on blood glucose and glucose tolerance. [19] It showed that after 5 weeks of feeding non-diabetic rats with sucrose, diabetic rats with sucrose, and diabetic rats with xylitol, the body weight and blood glucose significantly decreased, and the glucose tolerance ability of their bodies significantly increased in the group treated with xylitol compared to diabetic rats fed with sucrose. It showed that xylitol could be used as an anti-diabetic sugar substitute that can lower blood glucose levels.…”
Section: Introductionmentioning
confidence: 99%